Pengaruh Desain Kemasan Dan Ulasan Produk Terhadap Minat Beli Skintific Pada Shopee - Ameylia Alpina Damayanti; Era Agustina Yamini (CV. ITTC INDONESIA, 2025)
This study aims to determine the influence of packaging design and product reviews on consumer purchase intention for Skintific products on the Shopee e-commerce platform. In today's digital era, consumer purchasing decisions are influenced not only by product quality but also by visual factors such as packaging design and social media information such as product reviews. This study uses a quantitative approach, collecting data through distributing questionnaires to 400 respondents throughout Indonesia who have viewed or purchased Skintific products on Shopee. This study used a purposive sampling technique. The results show that packaging design and product reviews have a positive and significant effect on consumer purchase intention, partially. Attractive packaging design can increase visual appeal, while product reviews provide trust and a perception of quality for potential buyers.